Peruvian-British bilateral tightening in the infrastructure sector in Peru between 2017 and 2021 - Herrada Ruiz, Alvaro Alejandro (2024)
This article seeks to explain the reasons why Peru and the United Kingdom tightened their bilateral relationship in the infrastructure sector between 2017 and 2021. Therefore, it is proposed that the bilateral relationship became closer since the first G2G contract for Lima 2019 was signed due to factors at the Peruvian and British State level. On the one hand, the Brexit referendum, and the process of the United Kingdom’s exit from the European Union, meant the need to promote the export of British goods and services internationally. In this sense, in Peru, the British identified an opportunity to attract the import of their expertise in the infrastructure sector. On the other hand, on the Peruvian side, it is proposed that the infrastructure gap in the country has been a pending issue on the public agenda. It is concluded that the bilateral relationship became closer in the infrastructure sector, because the British needed to improve their positioning in Peru after Brexit and that coincided with the visibility of the infrastructure problems faced by Peru, which generated the conditions for the narrowing of the gap.